The Role of The Naqsabandiyah Khalidiyah wa Qadiriyah Order Practice in Strengthening The Values of Multicultural Islamic Education at The Darut Taqwa Islamic Boarding School in Mojokerto - Mohammad Khoirul Anam; Ahmad Ma’ruf; Askhabul Kirom (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2026)
The The objectives of this study are: 1. To describe the form of practice of the Naqsabandiyah Khalidiyah Wa Qadiriyah order applied in the lives of studens at the Darut Taqwa Ngembeh Dlanggu Mojokerto Islamic Boarding School 2. To analyze the implications of the practice of the Naqsabandiyah Khalidiyah Wa Qadiriyah order in strengthening multicultural Islamic education at the Darut Taqwa Ngembeh Dlanggu Mojokerto Islamic Boarding School. This study uses a qualitative approach, the type of research used is ethnographic research. Primary data sources were obtained from the caretaker of the Islamic boarding school and the mursyid of the Naqsabandiyah Khalidiyah Wa Qadiriyah order KH. M. Manshur Bahruddin, ustadz, congregation and students who follow the practice of the Naqsabandiyah Khalidiyah Wa Qadiriyah order. While secondary data sources were obtained from the books of scholars, the books of the Darut Taqwa Islamic boarding school order, books, and the results of relevant previous research. In this study, data collection techniques used observation, interview and documentation. Data analysis employed the Spradley model, which includes domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis.